Makna Dan Nilai Perkawinan Jujur Dalam Masyarakat Adat Wewewa Kabupaten Sumba Barat Daya - Ngongo, Maria Hendritha Lidya; Bustan, Fransiskus; Nope, Hotlif Arkilaus (Indonesian Journal of Teaching and Teacher Education, 2025)
This study aims to examine and interpret the meanings and values embedded in jujur marriage as practiced by the Wewewa community. Employing a qualitative ethnographic approach, data were collected through participant observation, in-depth interviews, and focus group discussions involving seven key informants selected purposively based on their cultural knowledge and social roles. Data were analyzed through stages of reduction, categorization, interpretation, and verification. The findings reveal that jujur marriage embodies three interrelated meanings: symbolic meaning, which reflects social status and respect for women; relational meaning, which strengthens kinship ties and social alliances; and spiritual-cultural meaning, which emphasizes the role of ancestors in sanctifying marriage. Furthermore, this tradition is underpinned by core values of responsibility, political legitimacy, cultural identity, familial solidarity, and religiosity. In conclusion, jujur marriage functions as an integrated cultural system that regulates marital relations while simultaneously reproducing indigenous values across generations, thereby sustaining the social structure and cultural identity of the Wewewa people in a changing social context.